Rice yield classification using Backpropagation Network - Puteh, Saad; Nor Khairah, Jamaludin; Siti Sakira, Kamrudin; Aryati, Bakri; Nursalasawati, Rusli (Penerbit Universiti Utara Malaysia, 2009)
Link to publisher's homepage at www.jict.uum.edu.my